Necrostatin-1 rescues mice from lethal irradiation - Huang, Zhentai (Biochim Biophys Acta, 2016)
There is emerging need in new medical products that can mitigate and/or treat the short- and long-term consequences of radiation exposure after a radiological or nuclear terroristic event. The direct effects of ionizing radiation are realized primarily via apoptotic death pathways in rapidly proliferating cells within the initial 1–2 days after the exposure. However later in the course of the radiation disease necrotic cell death may ensue via direct and indirect pathways from increased generation of pro-inflammatory cytokines. Here we evaluated radiomitigative potential of Necrostatin-1 after total body irradiation (TBI) and the contribution of necroptosis to cell death induced by radiation. Circulating TNFα levels were increased starting on d1 after TBI and associated with increased plasmalemma permeability in ileum of irradiated mice. Necrostatin-1 given iv. 48h after 9.5 Gy TBI attenuated radiation-induced receptor interacting protein kinase 3 (RIPK3) serine phosphorylation in ileum and improved survival vs. vehicle. Utilizing apoptosis resistant cytochrome c(−/−) cells, we showed that radiation can induce necroptosis, which is attenuated by RNAi knock down of RIPK1 and RIPK3 or by treatment with necrostatin-1 or -1s whereas 1-methyl-L-tryptophan, an indoleamine-2,3-dioxygenase inhibitor, did not exhibit radiomitigative effect. This suggests that the beneficial effect of necrostatin-1 is likely through inhibition of RIPK1-mediated necroptotic pathway. Overall, our data indicate that necroptosis, a form of programmed necrosis, may play a significant role in cell death contributing to radiation disease and mortality. This study provides a proof of principle that necrostatin–1 and perhaps other RIPK1 inhibitors are promising therapeutic agents for radiomitigation after TBI.